Barriers and Drivers of Digital Transformation among Tourism MSMEs. A Qualitative Exploration of Challenges, Adaptation Strategies, and Digital Readiness (International Journal of Multidisciplinary Research and Creative Innovation Ideas, 2026)
This research is based on the low level of digital transformation of tourism MSMEs, even though the adoption of digital technology is considered a key factor in competitiveness in the digital era. This study aims to analyze the influence of barriers to digital transformation in tourism, adaptation strategies to digital transformation, and digital readiness on the digital performance of tourism MSMEs through a quantitative approach. The research method combines a PRISMA-based Systematic Literature Review (SLR) adapted to identify relevant variables and indicators from Scopus-indexed journals (2021–2026), followed by quantitative research on a causal comparative design using questionnaires on tourism MSME actors around campus in Bali and tourists. The data was analyzed with Structural Equation Modeling (SEM) through SmartPLS 4 to test the relationship between barriers, adaptation strategies, digital transformation, digital readiness, and digital performance of tourism MSMEs. The results show that adaptation strategies play a strong role as a driver of digital transformation, while barriers have a negative impact, and digital readiness is a significant mediator in the relationship between digital transformation and the digital performance of tourism MSMEs. The main conclusion of this study is that the development of digital readiness and effective adaptation strategies is essential to increase the positive impact of digital transformation on tourism MSMEs. Contribution in the field lies in strengthening the quantitative basis for training program design, digital support policies, and strategies to strengthen the capacity of tourism MSMEs in the face of the digital transformation of the tourism sector